Influence of Marangoni convection, viscous dissipation, and variable fluid viscosity of nanofluid flow on stretching surface analytical analysis - Rehman, Ali; Khun, Ma Chau; Alsubaie, Abdullah Saad; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2024)
The current research paper investigates the viscous dissipation, influence of Marangoni convection (MC), and the variable fluid viscosity of nanofluid flow on stretching surfaces. The flow system takes into account variable viscosity with the impact of MC. Furthermore, velocity and temperature slips at the stretching surface are also considered in this study. To convert a collection of NLPDE to a NODE, we applied appropriate transformations. We utilize Homotopy analysis method (HAM) to solve this set of equations. The effects of temperature, tangential, and radial velocities on numerical perceptions involving Marangoni convection, nanoparticle volume friction, porosity parameter, Eckert number (EN) and heat source input factors are shown. A physical description is used to simulate and evaluate the structures of flow features such as velocity and temperature profiles in response to changes in developing factors. Based on the given result, we can observe that the temperature profile increases as EN and the heat source parameter increase, and that the velocity profile decreases as MC increases and increases with the porosity parameter.
Keywords: Al2O3-Cu/Water Hybrid Nanofluid; Entropy Generation Analysis; Heat-Transfer; Sheet